How the Wake Up Safe pediatric anesthesia collaborative increased quality improvement capability and collaboration. Issue 11 (20th May 2022) - Buck, David W.; Claure, Rebecca; Tjia, Imelda M.; Varughese, Anna M.; Brustowicz, Robert; Subramanyam, Rajeev
Abstract: Wake Up Safe is a patient safety organization consisting of 40 institutions with a mission to improve the processes of care and outcomes for newborns, infants, and children having anesthesia for surgery and medical procedures. It was recognized that the level of quality improvement (QI), knowledge, and experience varied greatly between member institutions. In Fiscal Year 2015, the group's leadership created a subcommittee on QI and education in efforts to provide member institutions with the skills and resources to use QI methodology to improve care at their own institution. This subcommittee developed a program to improve members' knowledge in safety analytics and QI science and to help members implement change in their own institutions. This review describes the development and implementation of this initiative. As a result of this initiative, significant progress was made improving the QI capability of the collaborative over a two‐year period. This educational and support program included workshops, an online discussion forum, site visits, and project presentations.